STUDI KEANEKARAGAMAN DAN STRUKTUR KOMUNITAS PERIFITON DI PERAIRAN SUNGAI COBAN RONDO MALANG - Zainal Abidin (G-Tech: Jurnal Teknologi Terapan, 2018)
Periphyton is a community of microorganisms that live attached to or adjacent to a substrate sink. For aquatic organisms, periphyton habitats have a relatively fixed. With it is so, the changes of water quality and substrate greatly affects the composition of his life and abundance. Periphyton composition and abundance depends on the tolerance or sensitivity to environmental changes. This study aims to determine each periphyton community in responding to changes in habitat quality by way of adjustment in community structure. The methodology used in this prektikum involves taking data from four stations along the river Coban Rondo, in each station there are 3 replicates. And take measurements of factors such environments as supportive data turbidity, flow rate, pH, and depth. Analyzed using Simpson's Dominance Index to determine the type of periphyton dominance, as well as morisita similarity indices and cluster analysis. The results showed that the diversity in each station belonging to the category of high (H more than 3.32) because the obtained value of the index H' between 3.2 to 3.48. Species that dominate from the four stations is Pinularia with an average Index Value Important (IVI) 31,5.